PENGARUH BIMBINGAN KEAGAMAAN TERHADAP PENCEGAHAN SIMPTOM NARCISSISTIC PERSONALITY DISORDER PADA REMAJA - Prasetiyo, Nova Tri; Rohim, Muhammad (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
The life of adolescents impacts not only themselves but also their surroundings, whether positively or negatively. Among the many negative traits that often occur in adolescents is Narcissistic Personality Disorder (NPD). This is because adolescence is a time of self-discovery. To prevent and minimize the symptoms of NPD, a concerted effort in the form of religious guidance is required. The goal is to delve deeper into the benefits and influences of Sufism education included in religious guidance when presented to them. The method used in this research is quantitative, with statistical calculations employing an associative or correlational research type. The results of this study show that the religious guidance received can be sufficiently applied by some of them. As for NPD, it can be said that they partly need efforts to avoid things related to the symptoms of this disorder. Based on the results of the study, it can be concluded that the research aligns with the initial hypothesis, namely that there is an influence on the prevention of Narcissistic Personality Disorder through the implementation of religious guidance in adolescents. Thus, it can be stated that if religious guidance is carried out to the fullest, the symptoms of NPD in students will also be lower.